Osteointegration of functionalised high-performance oxide ceramics: imaging from micro-computed tomography - Migliorini, Filippo; Eschweiler, Jörg; Betsch, Marcel; Maffulli, Nicola; Tingart, Markus; Hildebrand, Frank; Lecouturier, Sophie; Rath, Björn; Schenker, Hanno (Journal of Orthopaedic Surgery and Research, 2024)
Background: This study evaluated the osseointegration potential of functionalised high-performance oxide ceramics (HPOC) in isolation or coated with BMP-2 or RGD peptides in 36 New Zeeland female rabbits using micro-computed tomography (micro CT). The primary outcomes of interest were to assess the amount of ossification evaluating the improvement in the bone volume/ total volume (BV/TV) ratio and trabecular thickness at 6 and 12 weeks. The second outcome of interest was to investigate possible differences in osteointegration between the functionalised silanised HPOC in isolation or coated with Bone Morphogenetic Protein 2 (BMP-2) or RGD peptides. Methods: 36 adult female New Zealand white rabbits with a minimum weight of three kg were used. One-third of HPOCs were functionalised with silicon suboxide (SiOx), a third with BMP-2 (sHPOC-BMP2), and another third with RGD (sHPOC-RGD). All samples were scanned with a high-resolution micro CT (U-CTHR, MILabs B.V., Houten, The Netherlands) with a reconstructed voxel resolution of 10 µm. MicroCT scans were reconstructed in three planes and processed using Imalytics Preclinical version 2.1 (Gremse-IT GmbH, Aachen, Germany) software. The total volume (TV), bone volume (BV) and ratio BV/TV were calculated within the coating area. Results: BV/TV increased significantly from 6 to 12 weeks in all HPOCs: silanised (P = 0.01), BMP-2 (P < 0.0001), and RGD (P < 0.0001) groups. At 12 weeks, the BMP-2 groups demonstrated greater ossification in the RGD (P < 0.0001) and silanised (P = 0.008) groups. Trabecular thickness increased significantly from 6 to 12 weeks (P < 0.0001). At 12 weeks, BMP-2 promoted greater trabecular thickness compared to the silanised group (P = 0.07), although no difference was found with the RGD (P = 0.1) group. Conclusion: Sinalised HPOC in isolation or functionalised with BMP-2 or RGD promotes in vivo osteointegration. The sinalised HOPC functionalised with BMP-2 demonstrated the greatest osseointegration.
CRIS-Team Scopus Importer:2024-07-26
Keywords: Implants; Micro-CT; Ossification; Osteointegration